Hospital wastewater treated with a novel bacterial consortium (Alcaligenes faecalis and Bacillus paramycoides spp.) for phytotoxicity reduction in Berseem clover and tomato crops - Aneeba Rashid; Safdar A. Mirza; Ciara Keating; Sikander Ali; Luiza C. Campos (Water Science and Technology, 2021)
Hospital wastewaters are produced in large volumes in Pakistan (∼362–745 L/bed.day) and are discharged without proper treatment. They are widely used by farmers for crop irrigation and induce a phytotoxic effect on plant growth. The study was conducted to evaluate the effect of untreated and treated hospital wastewater on seed germination of a fodder crop Trifolium alexandrinum (Berseem clover) and a food crop Solanum lycopersicum (tomato). A bacterial consortium was formed with three bacterial strains, i.e., Alcaligenes faecalis and Bacillus paramycoides spp., which were individually proven efficient in previous studies. The concentrations of untreated and treated hospital wastewater (25, 50, 75 and 100%) were used to irrigate these crop seeds. To assess the efficiency of treatment, the germination percentage, delay index, germination index, stress tolerance indices, seedling vigour index and phytotoxicity index were calculated and were statistically proven significant. The seeds grown in treated wastewater concentrations showed negative values of phytotoxicity indices (tomato: −0.36, −0.47, −0.78 and −1.11; Berseem clover: −0.23) which indicate a stimulatory or non-toxic effect on seedling growth. Our work proposes that this bacterial consortium is efficient for hospital wastewater treatment before crop irrigation. HIGHLIGHTS Bacterial consortia proficiently used for hospital wastewater treatment.; Novel combination of Alcaligenes faecalis and Bacillus paramycoides spp. promotes the efficiency of hospital wastewater treatment.; Consortium proved to be capable of phytotoxicity reduction in two crop plants, Trifolium alexandrinum (Berseem clover) and Solanum lycopersicum (tomato), irrigated with treated hospital wastewater concentrations.;